The Impact Of Work Stress On Work Motivation, Employee Engagement And Turnover Intention Of Private Hospital Employees - Floretta Maulina Br Marpaung (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
The purpose of this study was to analyze the impact of work stress on work motivation, employee engagement and turnover intention in private hospitals. The population in this study were employees in private hospitals. The research sample consisted of 211 respondents. Data analysis using SEM PLS. The results showed that employee engagement had a negative effect on turnover intention, work stress had a positive effect on turnover intention. In addition, work motivation had a positive effect on employee engagement. However, the results also showed that motivation did not mediate the relationship between work stress and turnover intention. On the contrary, employee engagement was proven to be able to mediate work stress with turnover intention. The managerial implications that can be given are to create a more supportive work environment in improving internal communication, providing appropriate rewards, stress management by providing coping mechanism training, psychological consultation programs, providing monthly incentives, career development for outsourcing employees who have worked for more than 4-5 years, as well as increasing work flexibility and mentoring to reduce employee intentions to resign.